SISTEM SIMULASI PERHITUNGAN KPR DI PERUM PERUMNAS REGIONAL V BERBASIS WEB - Neilin Nikhlis; Dwi Setiawan (MANAJEMEN, 2021)
Perum Perumnas is a State-Owned Enterprise (BUMN) in the form of a Public Company (Perum). Perum Perumnas has 7 regional business areas and 1 rusunawa regional area. Perum Perumnas Regional V which is located at Jl. Wilis No. 23 Semarang is engaged in providing housing and settlements for the middle class community. In its business activities, Perumnas sells houses to the public with cash payment methods or through Home Ownership Credit (KPR). The Perumnas Branch can serve every consumer who comes to Perumnas Branch to seek information about the amount of monthly installment payments if the consumer applies the mortgage system with the down payment that the consumer has and the shortfall that must be paid. In carrying out this activity, the Perumnas Branch still uses the Microsoft Excel application.The problem that often arises at this time is the calculation of KPR between Perumnas Semarang Branch I and Perumnas Semarang Branch II which is quite different, making it less effective for companies. Based on this description, the author tries to provide a solution that is able to overcome these problems by designing a website-based mortgage calculation simulation system at Perum Perumnas Regional V with the aim of making it easier for consumers and marketing or sales parties to find information about mortgage calculations.Making this simulation system, the author uses the HTML, CSS, PHP, JavaScript and MySQL programming languages ​​as the database. In its manufacture, this application is adapted to the needs of Perumnas in general.The conclusion that can be drawn is the dissimilarity or difference in filling out the mortgage calculation where the Semarang Branch I and Semarang Branch II when the marketing staff does the mortgage calculation even though they use the same bank Suggestions that can be put forward is to create a mortgage calculation simulation system that can make it easier for consumers to get information about mortgage calculations quickly, efficiently and accurately and can be accessed anywhere and anytime.